Information Transmission in Groups: Peer Influence in High-Stakes, Irreversible Financial Decisions - Ahn, Tom; Cunha, Jesse M.; Veith, Patrick (The Review of Economics and Statistics, 2026)
We study the influence of workplace peers on a high-stakes, irreversible retirement plan choice. Midcareer U.S. military personnel choose between higher future pension payouts or an immediate bonus plus lower future payouts. With peers defined as those who have locked in their choices and personnel assignment rules ensuring that peer groups are exogenously formed, we capture the causal impact of peers. Greater peer take-up of the bonus, which is difficult to compare to the alternative plan but often extremely costly over one’s lifetime, discourages choosers from selecting the bonus. Peers have special impact within professional, race, and gender groups.